Physical Therapists' Perceptions and Use of Exercise in the Management of Subacromial Shoulder Impingement Syndrome: Focus Group Study. Issue 9 (1st September 2016) - Hanratty, Catherine E.; Kerr, Daniel P.; Wilson, Iseult M.; McCracken, Martin; Sim, Julius; Basford, Jeffrey R.; McVeigh, Joseph G.
Abstract: Background: Shoulder pain resulting from subacromial impingement syndrome (SAIS) is a common problem with a relatively poor response to treatment. There is little research exploring physical therapists' perspectives on the management of the syndrome. Objectives: The study objective was to investigate physical therapists' perceptions and experiences regarding the use of exercise in the treatment of patients with SAIS. Design: This was a qualitative focus group study. Methods: Three 60- to 90-minute focus group sessions containing 6 to 8 experienced musculoskeletal physical therapists (total number=20) were conducted. Thematic content analysis was used to analyze transcripts and develop core themes and categories. Results: Exercise was seen as key in the management of SAIS. The overarching theme was the need to "gain buy-in to exercise" at an early stage. The main subtheme was patient education. Therapists identified the need to use education about SAIS etiology to foster buy-in and "sell" self-management through exercise to the patient. They consistently mentioned achieving education and buy-in using visual tools, postural advice, and sometimes a "quick fix" of pain control. Furthermore, experienced practitioners reported including educational interventions much earlier in treatment than when they first qualified. Therapists emphasized the need for individually tailored exercises, including: scapular stabilization; rotator cuff, lower trapezius, and serratus anterior muscle strengthening; and anterior shoulder and pectoralis minor muscle stretching. Quality of exercise performance was deemed more important than the number of repetitions that the patients performed. Limitations: Expanding the geographical area over which the focus groups were conducted and including therapists with less than 5 years of postgraduate experience may have strengthened the findings of this study. Conclusion: Experienced musculoskeletal physical therapists believe that exercise is central in treating patients with SAIS and that gaining patient buy-in to its importance, patient education, promoting self-management, and postural advice are central to the successful treatment of people with SAIS.